103 A Randomised Trial Comparing Fish Oil (Smoflipid) vs. Olive Oil Lipid Emulsion (Clinoleic) in Preterm (< 30 Weeks) Neonates. (October 2012) - Deshpande, G; Deshmukh, M; Simmer, K; Mori, T; Croft, K; Kristensen, J
Abstract : Background: Fat emulsions used in Australia for PN in preterm neonates have been based on either soybean oil (SO) or olive oil (OO). OO based lipid Clinoleic has high ratio of n-6 to n-3 fatty acids (9:1) this may not be ideal for LC-PUFA supply. Newly available SMOFlipid has appropriate ratio n-6 to n-3 fatty acids (2.5:1). SMOFlipid also contains OO (25%), coconut oil (30%) and SO (30%). Better lipid clearance, reducing the risk of liver toxicity, reduced oxidative stress, lower immune-activity and anti-inflammatory effects are other potential advantages of SMOFlipid. Method: Preterm neonates (23–30 weeks) were randomised to receive Clinoleic or SMOFlipid emulsion for 7days using a standard protocol. Investigators and outcome assessors were masked to allocation. Plasma F2 -Isoprostanes (lipid peroxidation marker), RBC fatty acids, vitamin-E were measured before and after the study. Blood culture positive sepsis and growth was monitored for safety. Results: 30/34 participants (Clinoleic-15, SMOFlipid-15) completed the study. Both emulsions were well tolerated without any adverse events. F2 -isoprostane levels were reduced in SMOFlipid group as compared to baseline. Eicosapentanoic acid (EPA) and vitamin-E levels were significantly increased in SMOFlipid group. Oleic and Linoleic acid levels were increased in both groups. No significant differences were noted in post study Docosahexaenoic acid (DHA) levels in both groups despite higher levels of DHA in SMOFlipid. Conclusions: SMOFlipid was safe, well tolerated and also showed beneficial effect in terms of reduction of oxidative stress by reducing lipid peroxidation levels in high risk preterm neonates.